The metaphorical collecting of curiosities in early modern France and Germany - Kenny, N (Ashgate Publishing, Ltd., 2006)
This volume brings together an international group of scholars to investigate the various manifestations of, and relationships between, curiosity and wonder from the 16th to the 18th century.